The Shared Superintendency - Robert H. Decker; Adrian P. Talbot (Journal of Research in Rural Education, 1991)
Due to the heavy dependence upon agriculture in the state of Iowa the recession of the early 1980's, when combined with declining student numbers, has had a profound impact upon education. One consequence of these economic and social developments has been the growing number of school districts which have shared the services of a single superintendent. Based upon interviews with 41 of the 44 shared superintendents the authors were able to shed some light on some of the benefits and hardships associated with thes innovative administrative arrengement.